Local distance antimagic chromatic number for the union of star and double star graphs - Priyadharshini, V.; Nalliah, M. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 519.17 Let G=(V,E) be a graph on p vertices with no isolated vertices. A bijection f from V to {1,2,3,… ,p} is called a local distance antimagic labeling if, for any two adjacent vertices u and v, we receive distinct weights (colors), where a vertex x has the weight w(x)=olimits_vε N(x) f(v). The local distance antimagic chromatic number χ_lda(G) is defined as the least number of colors used in any local distance antimagic labeling of G. We determine the local distance antimagic chromatic number for the disjoint union of t copies of stars and double stars.